Use your head - "Buzan, Tony" (London, 1989)
Are you worried that you're not achieving your full potential? A few years after this classic book on how to improve your brainpower was first published, a fairly average student announced that he intended to try for a place at Cambridge University. His chances were assessed as slim', since his grades were usually unexceptional. But with the help of Use Your Head, he went on to achieve four As at A-level, two starred firsts at Cambridge and a top job with a multi-national company. Since 1974, Use Your Head has been translated into over 27 languages, has been published in five continents and 100 countries, has sold well over a million copies and still the demand increases! Use Your Head will: *Teach you the vital skills of Learning How to Think and Learn. *Increase your creative thinking and problem-solving capacity *Enable you to make the best of your brain *Provide you with both the confidence and the means to fulfil your own mental potential
Keywords: Psychology